2014
DOI: 10.1016/j.physbeh.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanistic insights into treadmill exercise based rescue of social defeat-induced anxiety-like behavior and memory impairment in rats

Abstract: Social defeat (SD) induced stress causes physiological and behavioral deficits in rodents, including depression and anxiety-like behaviors, as well as memory impairment. Anxiolytic and mood elevating effects of physical exercise are also known. However, rescue effect of physical exercise in social defeat-induced anxiety, depression or memory impairment has not been addressed. Role of epigenetic mechanisms that potentially contribute to these rescue or protective effects are also not known. Present study invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 99 publications
4
40
1
Order By: Relevance
“…The above-mentioned increase in the acetylation of histone H3 in the PFC is observed at 24 h after social defeat stress (Hinwood et al, 2011;Kenworthy et al, 2014). However consistent with our results, the long-lasting (about 2 weeks) change in the acetylation of histone H3 is also shown in the hippocampus after social defeat stress (Patki et al, 2014). It has been speculated that the histone acetylation in some brain areas including PFC correlates with susceptibility to social defeat stress (Kenworthy et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The above-mentioned increase in the acetylation of histone H3 in the PFC is observed at 24 h after social defeat stress (Hinwood et al, 2011;Kenworthy et al, 2014). However consistent with our results, the long-lasting (about 2 weeks) change in the acetylation of histone H3 is also shown in the hippocampus after social defeat stress (Patki et al, 2014). It has been speculated that the histone acetylation in some brain areas including PFC correlates with susceptibility to social defeat stress (Kenworthy et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have demonstrated that social defeat stress increases the acetylation of histone H3 in the median prefrontal cortex (PFC) (Hinwood et al, 2011;Kenworthy et al, 2014). However the others have reported that there is no significant increase in acetylation of histone H3 in the frontal cortex after social defeat stress (Hollis et al, 2010;Patki et al, 2014). It might be one of the reasons of discrepancy between these studies is that the former study evaluated the change in smaller cortical area than the latter study.…”
Section: Discussionmentioning
confidence: 99%
“…Data from human and animal studies suggest that sedentary, overindulgent lifestyles increase the risk of anxiety disorders and depression 155 and that IMS effected by exercise or IF can improve mood and ameliorate anxiety and depression 156159 . The ability of exercise to ameliorate symptoms of depression and anxiety is well known, and the underlying mechanisms have been elucidated, with upregulation of BDNF expression in neuronal circuits that regulate mood playing a role 160162 .…”
Section: Ims and Neurological Disordersmentioning
confidence: 99%
“…Physical exercise has been shown to improve cognitive responses to psychosocial stress and rescue rats from social defeat-induced anxiety-like behaviour and memory impairment ). This beneficial effect might potentially be mediated by epigenetic mechanisms, including exercise-induced H3 acetylation and modulation of methylation in the hippocampus (Patki et al 2014).…”
Section: Discussionmentioning
confidence: 99%